THE RUSSIAN-MONGOLIAN BORDER ZONE: A STUDY OF THE CURRENT STATUS AND CHALLENGES OF DEVELOPMENT AT THE MUNICIPAL LEVEL - Potaev, Victor; Atanov, Nikolay; Subanakov, Georgiy; Tsyrenov, Dashi (Revista Inclusiones, 2020)
The border-zone areas in the aggregate of five municipal districts, as well as their place in the regional economy and intermunicipal characteristics, are considered for the first time ever. It is found that the existing preferences (geographical and territorial) for entering into the international division of labor and cross-border cooperation are not currently used enough. It is revealed that the border location imposes on municipalities and their population additional loads, and emergency situations, the implementation of which is within the competence of the federal authorities rather than local government.